Returnee STEM scholars from Japan: Impacts on research capacity and internationalization in Chinese universities - Zhang, Xixi; Enkhtur, Ariunaa (American Journal of STEM Education, 2026)
This study explores Chinese STEM graduates from Japanese universities who returned to China, highlighting their significant contributions to education, research, and international collaboration at home institutions. Findings reveal that returnees significantly enhance laboratory standards, graduate education quality, research, and international collaborations at their home institutions. They apply Japanese-style supervision methods, facilitate global academic partnerships, and elevate their institutions’ international standing. However, challenges persist, including limited research time, frequent evaluations, and political influences on academic exchanges. Social networks within academia also affect the implementation of new programs. Despite these challenges, returnees contribute to patent development, technological advancements, demonstrating their broader societal impact.